2010
DOI: 10.1186/1476-4598-9-275
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 acetylation is associated with loss of DNA binding at promoters associated with cell cycle arrest and cell death in a colon cell line

Abstract: Butyrate, a known histone deacetylase inhibitor (HDACi) and product of fibre fermentation, is postulated to mediate the protective effect of dietary fibre against colon cancer. The transcription factor Sp1 is a target of acetylation and is known to be associated with class I HDACs, including HDAC1. Sp1 is a ubiquitous transcription factor and Sp1-regulated genes include those involved in cell cycle regulation, apoptosis and lipogenesis: all major pathways in cancer development. The only known acetylated residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 39 publications
3
82
0
1
Order By: Relevance
“…A model was proposed in which inhibition of Sp1-/Sp3-associated HDAC activity leads to induction of histone acetylation and transcriptional activation of p21 WAF1 [86] . It was verified that cell growth arrest at G 2 and apoptosis induction by butyrate (1-10 m M ) in HCT116 human colon cancer cells were associated with p21 WAF1 and Bak overexpression [87] . More specifically, butyrate increased the acetylation of Sp1, and this resulted in decreased binding to these gene promoters, indicating that non-histone proteins also represent relevant targets for the anticancer actions of this HDACi [87] .…”
Section: Butyratementioning
confidence: 98%
See 1 more Smart Citation
“…A model was proposed in which inhibition of Sp1-/Sp3-associated HDAC activity leads to induction of histone acetylation and transcriptional activation of p21 WAF1 [86] . It was verified that cell growth arrest at G 2 and apoptosis induction by butyrate (1-10 m M ) in HCT116 human colon cancer cells were associated with p21 WAF1 and Bak overexpression [87] . More specifically, butyrate increased the acetylation of Sp1, and this resulted in decreased binding to these gene promoters, indicating that non-histone proteins also represent relevant targets for the anticancer actions of this HDACi [87] .…”
Section: Butyratementioning
confidence: 98%
“…It was verified that cell growth arrest at G 2 and apoptosis induction by butyrate (1-10 m M ) in HCT116 human colon cancer cells were associated with p21 WAF1 and Bak overexpression [87] . More specifically, butyrate increased the acetylation of Sp1, and this resulted in decreased binding to these gene promoters, indicating that non-histone proteins also represent relevant targets for the anticancer actions of this HDACi [87] . Because of its HDAC-inhibitory effects, butyrate has been considered for combinatorial anticancer interventions with diverse agents, including dietary and synthetic DNMT inhibitors [88] and retinoids [89] .…”
Section: Butyratementioning
confidence: 98%
“…In addition, HDACs can influence the degree of acetylation of nonhistone proteins such as transcription factors, thus modulating their activity with consequent effects on cellular phenotype. For example, the transcription factor SP1 is known to be associated with Class I HDACs (28), and recent studies have shown that its acetylation is associated with an up-regulation of p21 waf in colonic epithelial cells (29). One of the factors linked to the uncontrolled proliferation of IPF fibroblasts involves reduced levels of the antifibrotic lipid mediator prostaglandin E2 as a consequence of diminished cyclooxygenase-2 (COX-2) expression (30).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate, a common gut microbiome byproduct, and propionate can inhibit histone deacetylase (HDAC) enzymes and alter the expression of specific genes via conformational changes in the active site of HDAC leading to its inactivation (Aoyama, Kotani, & Usami, 2010; Dashwood, Myzak, & Ho, 2006). Microbe-derived butyrate can trigger cell cycle arrest and apoptosis in rapidly dividing colonocytes, and thus has proven effective at preventing colon cancer (Rooks & Garrett, 2011; Shenderov, 2012; Waby, et al, 2010). In vitro studies have shown that butyrate amplifies the antioxidant properties of glutathione-S-transferase (Ebert, et al, 2003).…”
Section: Biomarkers Of Interestmentioning
confidence: 99%